Anticancer Properties of Essential Oils: An Overview - Andrade, Milene A.; Braga, Mariana Aparecida; Cesar, Pedro H. S.; Trento, Marcus Vinicius Cardoso; Espósito, Mariana Araújo; Silva, Lucilene Fernandes; Marcussi, Silvana (Current Cancer Drug Targets, 2018)
Background: Essential oils are complex mixtures of low molecular weight compounds extracted from plants. Their main constituents are terpenes and phenylpropanoids, which are responsible for their biological and pharmaceutical properties, such as insecticidal, parasiticidal, antimicrobial, antioxidant, anti-inflammatory, analgesic, antinociceptive, anticarcinogenic, and antitumor properties. Cancer is a complex genetic disease considered as a serious public health problem worldwide, accounting for more than 8 million deaths annually. Objective: The activities of prevention and treatment of different types of cancer and the medicinal potential of essential oils are addressed in this review. Conclusion: Several studies have demonstrated anti-carcinogenic and antitumor activity for many essential oils obtained from various plant species. They may be used as a substitution to or in addition to conventional anti-cancer therapy. Although many studies report possible mechanisms of action for essential oils compounds, more studies are necessary in order to apply them safely and appropriately in cancer therapy.
Keywords: phenylpropanoids